THE TRANSFORMATION OF ABU YUSUF'S FISCAL PRINCIPLES: FORMULATING INCLUSIVE SHARIA POLICIES FOR ECONOMIC STABILITY AND WELFARE IN DEVELOPING COUNTRIES - Isro, Arsan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Developing countries face income inequality, limited fiscal space, and low financial inclusion. This condition demands fair, sustainable, and inclusive fiscal policies. This study aims to formulate a contemporary, inclusive Islamic fiscal policy model based on the principles of public finance in Abu Yusuf's thought. In the context of economic challenges in developing countries, such as distribution inequality, fiscal instability, and the limited reach of conventional financial systems, classical Islamic thought is considered to have strategic relevance. This study employs a qualitative approach, incorporating a literature review and conceptual analysis of the work Kitab al-Kharaj, as well as contemporary fiscal policy literature. The results demonstrate that Abu Yusuf's principles, including distributive justice, collection efficiency, and state accountability, can be effectively implemented in the design of Islamic fiscal policy, promoting social inclusion and economic stability. This study presents a conceptual model of fiscal policy grounded in the maqasid sharia, emphasising equity and financial sustainability. These findings contribute to the advancement of Islamic fiscal policy theory and offer normative recommendations for the development of public policy in developing countries.